Perancangan Motion Graphic Batik Incung Kabupaten Kerinci - Novian, Donie; Rochmawati, Irma (Fakultas Desain Universitas Komputer Indonesia, 2022)
Many regions in Indonesia produce batik with their own characteristics, one of which is Incung batik from Kerinci Regency, precisely in the city of Sungai Penuh, Jambi Province. At first, Incung batik itself was made only by writing the characters and the colors used were generally dark red and black. However, now that it has many variants of colors and motifs, the coloring materials commonly used are materials derived from nature and synthetic materials. The motifs applied to the Incung batik today, originally came from writing (scripts) which had begun to be less well known by the people of Kerinci Regency, especially among the younger generation, the Incung script was used by the Kerinci people in ancient times to document history, write literature, spells, as well as customary law written on palm leaves, bamboo, and buffalo horns. Therefore, the designer tries to use information media in the form of animation media to attract attention as well as increase knowledge and increase public insight, especially the younger generation in Kerinci Regency so that they are more familiar with Incung batik itself.